Directed Networks as a Novel Way to Describe and Analyze Cardiac Excitation: Directed Graph Mapping - Vandersickel, Nele; Van Nieuwenhuyse, Enid; Van Cleemput, Nico; Goedgebeur, Jan; El Haddad, Milad; De Neve, Jan; Demolder, Anthony; Strisciuglio, Teresa; Duytschaever, Mattias; Panfilov, Alexander V. (Frontiers in Physiology, 2019)
Networks provide a powerful methodology with applications in a variety of biological, technological and social systems such as analysis of brain data, social networks, internet search engine algorithms, etc. To date, directed networks have not yet been applied to characterize the excitation of the human heart. In clinical practice, cardiac excitation is recorded by multiple discrete electrodes. During (normal) sinus rhythm or during cardiac arrhythmias, successive excitation connects neighboring electrodes, resulting in their own unique directed network. This in theory makes it a perfect fit for directed network analysis. In this study, we applied directed networks to the heart in order to describe and characterize cardiac arrhythmias. Proof-of-principle was established using in-silico and clinical data. We demonstrated that tools used in network theory analysis allow to determine the mechanism and location of certain cardiac arrhythmias. We show that the robustness of this approach can potentially exceed the existing state-of-the art methodology used in clinics. Furthermore, implementation of these techniques in daily practice can improve accuracy and speed of cardiac arrhythmia analysis. It may also provide novel insights in arrhythmias that are still incompletely understood.